Coding Scheme for Assessment of Students' Explanations and Predictions - Mihael Gojkošek; Gorazd Planinšič; Josip Sliško (Karolinum Press, 2017)
In the process of analyzing students' explanations and predictions for interaction between brightness enhancement ﬁlm and beam of white light, a need for objective and reliable assessment instrumentarose. Consequently, we developed a codingscheme that was mostly inspired by the rubrics for self-assessment of scientiﬁc abilities. In the paper we present the grading categories that were integrated in the coding scheme, and descriptions of criteria used for evaluation of students work. We report the results of reliability analysis of new assessment tool and present some examples of its application.